Determinants of the Financial Statements Quality of the Ministry at the State Treasure Services Office - R.A. Rahayu Suryanti; Gede Adi Yuniarta; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2022)
This study aims to examine and analyze the effect of HR competence, the use of information technology, and the reconciliation process on the quality of financial reports, to examine and analyze the influence of HR competence to the use of information technology, and to examine and analyze the effect of HR competence on the reconciliation process. Methods of data collection using a questionnaire. The research population is all financial managers and financial statement preparers who are involved and responsible for the reconciliation process and the preparation of financial reports in the work units within the KPPN Denpasar, KPPN Singaraja, and KPPN Amlapura as many as 668 people. The number of research samples was 250 people who were selected using the Slovin formula. The results showed that HR competence, utilization of information technology, and the reconciliation process had a significant positive effect on the quality of financial reports, HR competence had a significant positive effect on the use of information technology, and HR competence had a significant positive effect on the reconciliation process.